Pengembagan Metode Pengajaran Tafsir di Pesantren - Bisri, Hasan (TAJDID, 2019)
By using reflective methods, this article seeks to elaborate the methods of interpretive learning in Islamic boarding schools. In developing methodological learning, it seems that the munâzharah method is the most appropriate, because this method can bring up bold and critical thinking on something that is already considered standard, so that creativity and innovation will develop brilliantly. The material being studied at pesantren is the interpretation of the Koran which is textualized in the classical books (al-turâts) which are now popularly known as the kitab kuning. From this book, the students absorb and draw religious knowledge to be developed and applied in society. With the development of modern scientific studies and the rapid growth of science and technology and economy accompanied by various social problems, the development of teaching methods and interpretation studies in pesantren must be renewed and refined, such as the munâzharah. With this method, teaching interpretations can stimulate the active involvement of students, both intellectually and emotionally, so that brilliant ideas emerge.